THE INFLUENCE OF AIR DENSITY ON RECEIVED LASER SIGNALS: THE INFLUENCE OF AIR DENSITY ON RECEIVED LASER SIGNALS - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is to make a correct assessment of the atmospheric parameters and to choose a model for their removal, achieving the required accuracy and high productivity with minimal material costs when conducting laser measurements.